APAKAH PROFITABILITAS MAMPU MEMODERASI PENGARUH ESG DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN PEMBAYARAN DIVIDEN? - Septiana, Fanny; Handayani, Sri (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
Decisions regarding dividend policy can potentially increase shareholder prosperity but can also reduce internal funding sources for the company. This research investigates the impact of Environmental Social Governance (ESG) and Investment Opportunity Set (IOS) on dividend payment policy and profitability as moderating factors. A causal design with Moderated Regression Analysis (MRA) is used in the Wholesale Trade sector listed on the Indonesia Stock Exchange during 2019-2022. A total of 64 sample data have met the criteria for distributing dividends during the research year. The research results show that ESG and profitability increase dividend payment policies, but IOS does not influence dividend payment policies. Furthermore, profitability can weaken the influence of ESG on dividend payment policy but strengthen the impact of IOS on dividend payment policy. The findings explain the role of profitability, which results from social activities and investment in moderating dividend payment policies. This research provides relevant theoretical contributions to the bird in the hand theory and flexible dividend policy.